Subjective Areas of Life Quality for People in Different Situa-tion in the Context of Sustainable Development - Rożnowska, Anna (Problemy Ekorozwoju, 2011)
The paper presents data referring to subjective areas of the quality of life of healthy people living in comfortable external conditions and of those living under chronic stress, of the people suffering from cancer and the homeless. The data is examined in the perspective of sustainable development, in particular at the social level of the theory. The results of the study indicate that people with normal living conditions, that is extramural and postgraduate students, achieve significantly higher results in the domain of life satisfaction and its particular aspects, optimism, the sense of meaning in life, the sense of coherence, problem-focused style of coping with stress. Statistically, they also show remarkably lower results in the domain of emotion-focused style of stress management.